A novel method for real-time analysis of the complement C3b:FH:FI complex reveals dominant negative CFI variants in age-related macular degeneration - Hallam, Thomas M.; Cox, Thomas E.; Smith-Jackson, Kate; Brocklebank, Vicky; Baral, April J.; Tzoumas, Nikolaos; Steel, David H.; Wong, Edwin K. S.; Shuttleworth, Victoria G.; Lotery, Andrew J.; Harris, Claire L.; Marchbank, Kevin J.; et al. (Frontiers in Immunology, 2022)
Age-related macular degeneration (AMD) is linked to 2 main disparate genetic pathways: a chromosome 10 risk locus and the alternative pathway (AP) of complement. Rare genetic variants in complement factor H (CFH; FH) and factor I (CFI; FI) are associated with AMD. FH acts as a soluble cofactor to facilitate FI’s cleavage and inactivation of the central molecule of the AP, C3b. For personalised treatment, sensitive assays are required to define the functional significance of individual AP genetic variants. Generation of recombinant FI for functional analysis has thus far been constrained by incomplete processing resulting in a preparation of active and inactive protein. Using an internal ribosomal entry site (IRES)-Furin-CFI expression vector, fully processed FI was generated with activity equivalent to serum purified FI. By generating FI with an inactivated serine protease domain (S525A FI), a real-time surface plasmon resonance assay of C3b:FH:FI complex formation for characterising variants in CFH and CFI was developed and correlated well with standard assays. Using these methods, we further demonstrate that patient-associated rare genetic variants lacking enzymatic activity (e.g. CFI I340T) may competitively inhibit the wild-type FI protein. The dominant negative effect identified in inactive factor I variants could impact on the pharmacological replacement of FI currently being investigated for the treatment of dry AMD.